PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PEMBELAJARAN RADEC DI KELAS III SDN 081224 SIBOLGA - Rahayu, Shintia; Yesi Anita; Reinita; Mansurdin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study is the low learning outcomes of grade III students. The problem in this study is how to apply the RADEC learning model to improve the learning outcomes of Pancasila Education students of SDN 081224 Sibolga. This research is a Class Action Research (PTK) aimed to find out the process and results of the application of the RADEC model to grade III students of SDN 081224 Sibolga on different materials that are beautiful. The approaches used in the research are quantitative and qualitative approaches. The data collection techniques used are observation, test and non-test . The subjects of the study were classroom teachers and students totaling 17 people consisting of 10 males and 7 females. The research was carried out in two cycles. In the first cycle, the results of the research on the learning process were at a good qualification (B) and the percentage of completeness of the learning test results was 62,9%. In the second cycle, the results of the research on the learning process increased at very good qualifications (A) and the percentage of completeness of the learning test results was 80.58%. The conclusion of this study is that the application of the RADEC model can improve the learning process and outcomes of Pancasila Education for grade III students of SDN 081224 Sibolga.